2022
DOI: 10.12688/f1000research.128506.1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of unwillingness or inaccessibility to receive the COVID-19 vaccination among persons with disabilities in Bangladesh

Abstract: Introduction Persons with disabilities (PWDs) are among the most vulnerable communities to suffer the serious consequences of COVID-19, and accepting COVID-19 vaccination is one of the recommended health advisories for them. Unwillingness to receive vaccines is a concerning issue, especially in the countries of Southeast Asia. The study aims to find out the COVID-19 vaccination rate of persons with disabilities (PWDs) in Bangladesh, the rate of unwillingness or inaccessibility of vaccination for PWDs, and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is likely that a subset of participants did not receive any doses due to hesitancy towards the COVID-19 vaccine. Previous studies found a small but substantial proportion of people with disabilities had reluctance towards COVID-19 vaccines [45][46][47]. Thus, addressing the misconceptions and social barriers of people with disabilities is crucial in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that a subset of participants did not receive any doses due to hesitancy towards the COVID-19 vaccine. Previous studies found a small but substantial proportion of people with disabilities had reluctance towards COVID-19 vaccines [45][46][47]. Thus, addressing the misconceptions and social barriers of people with disabilities is crucial in this regard.…”
Section: Discussionmentioning
confidence: 99%